STRUKTUR KOMUNITAS IKAN KARANG PADA TEKNOLOGI ATRAKTOR MULTIFUNGSI DI PERAIRAN KAHYAPU, ENGGANO, BENGKULU - Zamdial Zamdial; Nurlaila Ervina Herliany; Wahyu Nurmansyah; Ali Muqsit (Jurnal Teknologi Perikanan dan Kelautan, 2020)
Multifunctional attractor technology is a technology of enriching fish resource stock in a water. This research aims to calculate and analyze the structure of coral fish communities associated in the waters of Kahyapu Village, Enggano Island, Bengkulu. The research was conducted in March-April 2020. The data was collected using Underwater Visual Census (UVC) techniques and underwater camera using SCUBA equipment. The method used in this study was a survey method. The relationship between reef fish abudance and immersiontime in multifunction attractor technology was analyzed by simple linier regression. It found 1.041 individuals from 43 species of 15 coral fish families associated with, consisting of 13 target fish species, 5 species of indicator fish, and 25 species of major fish groups. The composition of the species was found species with highest number of individuals from Dascyllus trimaculatus of 11,82%. Abundance of coral fish (X) amounts to 1,19 individuals/m3. The value of the diversity index was (H’) 3,25. The evenness index (E) value was 0,863. Meanwhile, the dominant index value (C) was in the range of 0,0019-0,2363. The value of the three indexes are high diversity and evenness but no fish dominates. The result of a simple linear regression analysis was Y=1,3639x+130,89 (R2=0,0807, r=0,284, F=0,439, and Ftable=6,61). Water parameters at the research location are very suitable for the life of coral biota.